i-PRESTIGE: 2021 Annual Report Research, Industrial Linkages and Alumni Division UiTM Cawangan Johor / Research, Industrial Linkages and Alumni Division Universiti Teknologi MARA Cawangan Johor - Sa’udah @ Suhadak, Nurulzulaiha; Samsudin, Aidarohani; Zainon, Saunah; Tan, Yan Ling; Sa'udah @ Suhadak, Nurulzulaiha; Mokhtar, Nurkhairany Amyra; Mat Kamal, Siti Nuur-Ila; Mazan, Diana'; Isahak, Siti Nordiyana; Bachok, Mohd Fairuz; Md Isa, Kamariah; Mohamad, Saiful Najmee; et al. (Research, Industrial Linkages and Alumni Division, Universiti Teknologi MARA Cawangan Johor, 2021)
This annual report of the Research, Industrial Linkages and Alumni (PJI&A) Division, UiTMCJ, known as i-PRESTIGE, the fourth publication of i-PRESTIGE 2021 acts as a guidance towards providing information on all activities, achievements and the performance of the year 2021.